2012
DOI: 10.1073/pnas.1210037109
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor as a master regulator of the c-MYC/MXD1 network

Abstract: Vitamin D signaling regulates cell proliferation and differentiation, and epidemiological data suggest that it functions as a cancer chemopreventive agent, although the underlying mechanisms are poorly understood. Vitamin D signaling can suppress expression of genes regulated by c-MYC, a transcription factor that controls epidermal differentiation and cell proliferation and whose activity is frequently elevated in cancer. We show through cell-and animal-based studies and mathematical modeling that hormonal 1,2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
81
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(94 citation statements)
references
References 58 publications
7
81
0
1
Order By: Relevance
“…In agreement with these studies, we found that VDR deletion, which increases EGFR signals, also significantly enhanced nuclear βcatenin in malignant colonocytes, 49.2±11.3% in tumors from Vdr /− vs. 28.8±7.1% in tumors from Vdr +/+ mice (Fig 2C, p<0.05, n=4 adenomas/genotype). Not surprisingly, βcatenin targets, Myc and cyclin D1 (6, 39, 40) were also increased in Vdr −/− tumors (Figs 2A-B) consistent with reports that vitamin D signals suppress Myc and cyclin D1 in colon cancer cells (41, 42). …”
Section: Resultssupporting
confidence: 91%
“…In agreement with these studies, we found that VDR deletion, which increases EGFR signals, also significantly enhanced nuclear βcatenin in malignant colonocytes, 49.2±11.3% in tumors from Vdr /− vs. 28.8±7.1% in tumors from Vdr +/+ mice (Fig 2C, p<0.05, n=4 adenomas/genotype). Not surprisingly, βcatenin targets, Myc and cyclin D1 (6, 39, 40) were also increased in Vdr −/− tumors (Figs 2A-B) consistent with reports that vitamin D signals suppress Myc and cyclin D1 in colon cancer cells (41, 42). …”
Section: Resultssupporting
confidence: 91%
“…There is a clear precedent for this action, because many nuclear receptors including those for the estrogens and androgens exhibit properties such that they are activated through mechanisms independent of their cognate ligands (43)(44)(45)(46)(47). With respect to the VDR, there are numerous hints of this possibility as well, associated directly with the receptor's ability to interact with the specific transcription factor targets of other signaling pathways both on or off DNA (18,19); a recent report that the role of VDR in fat cell differentiation may be dissociated from the influence of 1,25(OH) 2 D 3 [independent of 1,25(OH) 2 D 3 ] may also be relevant and deserving of further exploration (48). Interestingly, a recent analysis of VDR binding sites on a genome-wide scale has revealed that although the vast majority are induced by 1,25(OH) 2 D 3 , relatively robust levels of VDR can be found in the absence of 1,25(OH) 2 D 3 at a rather substantial number of sites on the genome (13,21,22,49).…”
Section: Discussionmentioning
confidence: 96%
“…One possibility is that in vivo VDR binding is modulated by protein-protein interactions with co-factors: SP1 and ETS1 are known to modulate VDR binding, and there is some evidence that interactions between SP1 and VDR may enable modulation of genes that lack a classical VDR recognition motif [43,44]. Several other proteins are known to bind in association with VDR, including NR4A1 and c-MYC [45,46]. CTCF is known to modulate DNA binding via protein-protein interactions with other nuclear receptors [47-49].…”
Section: Discussionmentioning
confidence: 99%